2002
DOI: 10.1029/2001jd000641
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aerosol and thin film spectra of supercooled ternary solution aerosol

Abstract: [1] Extinction spectra of H 2 SO 4 -HNO 3 -H 2 O supercooled ternary solution (STS) aerosol particles, fully covering the mid-and near-infrared region from 750 to 13,000 cm À1 (13.9 to 0.7 mm), have been measured in the laboratory using a 75 dm 3 volume coolable aerosol cell coupled with a Fourier transform spectrometer. The STS spectra were recorded at temperatures close to those encountered in the polar stratosphere and were fitted to a spectrum modelled by combining Mie scattering theory and published thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…So far, only the mixing scheme developed by Biermann et al (2000) permits the calculation of optical constants in the STS system which cover a broad range of compositions and temperatures. However, as recently shown by McPheat et al (2002) on the basis of a measured extinction spectrum of STS aerosols of approximately 21 wt% H 2 SO 4 and 12 wt% HNO 3 at around 182 K, the Mie calculation using the Biermann et al (2000) optical constants differed significantly from the experimental spectrum in the important 750-1300 cm −1 region. They proposed that the temperature dependence of the sulphate feature in this regime might explain the poor Mie fit, since the H 2 SO 4 /H 2 O binary optical constants needed in the mixing scheme to calculate the ternary refractive indices were only measured down to 253 K. But note that the calculation of the ternary refractive indices of STS particles with 21 wt% H 2 SO 4 and 12 wt% HNO 3 using the Biermann et al (2000) mixing rule does not require optical constants for a binary solution containing 21 wt% H 2 SO 4 (which were in fact only measured down to 253 K), but for a binary solution containing 33 wt% H 2 SO 4 (corresponding to 21 wt% H 2 SO 4 +12 wt% HNO 3 in the ternary STS particles) which is accessible down to 193 K in the data base of Biermann et al (2000).…”
Section: Discussionmentioning
confidence: 80%
“…So far, only the mixing scheme developed by Biermann et al (2000) permits the calculation of optical constants in the STS system which cover a broad range of compositions and temperatures. However, as recently shown by McPheat et al (2002) on the basis of a measured extinction spectrum of STS aerosols of approximately 21 wt% H 2 SO 4 and 12 wt% HNO 3 at around 182 K, the Mie calculation using the Biermann et al (2000) optical constants differed significantly from the experimental spectrum in the important 750-1300 cm −1 region. They proposed that the temperature dependence of the sulphate feature in this regime might explain the poor Mie fit, since the H 2 SO 4 /H 2 O binary optical constants needed in the mixing scheme to calculate the ternary refractive indices were only measured down to 253 K. But note that the calculation of the ternary refractive indices of STS particles with 21 wt% H 2 SO 4 and 12 wt% HNO 3 using the Biermann et al (2000) mixing rule does not require optical constants for a binary solution containing 21 wt% H 2 SO 4 (which were in fact only measured down to 253 K), but for a binary solution containing 33 wt% H 2 SO 4 (corresponding to 21 wt% H 2 SO 4 +12 wt% HNO 3 in the ternary STS particles) which is accessible down to 193 K in the data base of Biermann et al (2000).…”
Section: Discussionmentioning
confidence: 80%
“…Physical properties of both HNO 3 and H 2 SO 4 solutions [2] under stratospheric conditions are previously carried out. Infrared optical constants of this ternary system for different mixtures of H 2 SO 4 and HNO 3 solutions [3][4][5] are evaluated at stratospheric temperature range [6][7][8][9] from 183 K to 293 K. Furthermore, four data sets are tested in the H 2 SO 4 /H 2 O system as well as two data sets in the HNO 3 /H 2 O system [10][11][12][13] revealing partly significant discrepancies in aerosol properties with those parameters recovered from FTIR spectra in the literature data. Rapid temperature fluctuations are shown to cause liquid H 2 SO 4 /HNO 3 /H 2 O stratospheric aerosols [14] to depart considerably from thermodynamic equilibrium.…”
Section: Introductionmentioning
confidence: 96%
“…This approach has already been implemented in several retrieval algorithms in remote sensing applications. , However, there is still a need for an independent study to assess the accuracy by which FTIR extinction spectra of STS aerosols can be analyzed in terms of aerosol composition and mass concentration on the basis of this mixing rule. McPheat et al have observed large spectral differences between a measured STS droplet extinction spectrum and a Mie calculation using the Biermann et al mixing rule in the 750−1300 cm -1 spectral region. However, this must not be a result of a deficiency of the mixing rule but may be fully explained by the poor quality of the Biermann et al binary data sets, which were employed in the mixing rule calculation.…”
Section: Introductionmentioning
confidence: 99%